Recent progress in flexible organic solar cells - Shitong Li; Zhixiang Li; Xiangjian Wan; Yongsheng Chen (eScience, 2023)
Photovoltaic cells are one of the most promising renewable energy sources to address energy and environmental issues. Amongst the many photovoltaic technologies, organic solar cells (OSCs) have numerous advantages, such as low cost, light weight, semi-transparency, and flexibility. This last is a special merit of OSCs, arising due to the intrinsic flexibility of organic active layers. With promising applications in fields such as building-integrated photovoltaics and wearable electronics, flexible OSCs (F-OSCs) have developed rapidly, and significant process has been made in recent years. In this review, we summarize the recent progress in F-OSCs from the perspective of flexible transparent electrodes. In addition, large-area F-OSCs and their potential applications are briefly discussed. Finally, challenges for the further development of F-OSCs are presented.